Catalyst for adsorption-photo-thermal synergistic degradation of VOCs (volatile organic compounds) and preparation method of catalyst
By constructing TiO2@MnO2@GCS catalyst on hollow carbon spheres, combining photocatalysis and thermal catalysis, the problems of high energy consumption and low quantum efficiency in traditional technology are solved, and efficient degradation of high concentration VOCs is achieved, suitable for industrial use Removal of VOCs.
Patent Information
- Application Number
- CN202411392124.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-17
AI Technical Summary
The existing thermal catalytic oxidation technology has high energy consumption, the photocatalytic oxidation technology has low quantum efficiency, and the band gap of traditional TiO2 catalysts limits its application in photothermal catalytic reactions, making it difficult to effectively degrade high-concentration VOCs.
Using hollow carbon spheres as the support framework, MnO2 and TiO2 were introduced through microwave-hydrothermal method to prepare the TiO2@MnO2@GCS catalyst of core-shell structure. Combined with photocatalysis and thermal catalysis, an adsorption-photothermal synergistic catalytic system was formed to improve the Degradation efficiency of high concentrations of VOCs.
It has achieved efficient adsorption and degradation of variable concentration VOCs, overcomes the problems of high energy consumption and low quantum efficiency in traditional technology, and is suitable for efficient removal of industrial VOCs, especially in wet environments, which show good catalytic performance.
Smart Images

Figure CN119318954A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of industrial organic waste gas treatment, and in particular to a catalyst for adsorption-photothermal synergistic degradation of VOCs and a preparation method thereof. Technical Background
[0002] Volatile organic compounds (VOCs) are key precursors of environmental pollution such as haze and photochemical smog. They not only cause serious pollution to the ecological environment, but also have serious toxic effects on the human cardiovascular and respiratory systems. VOCs control has become an environmental problem that needs to be solved urgently, and has also become the key and focus of air pollution control.
[0003] At present, the mainstream technologies for VOCs end-of-pipe treatment are adsorption recovery and catalytic oxidation. Catalytic oxidation is the oxidation and decomposition of VOCs into non-toxic CO2 and H2O under the action of catalysts, and is one of the most effective treatment methods at present. Catalytic oxidation mainly includes thermal catalytic oxidation technology, photocatalytic oxidation technology and photothermal synergistic oxidation technology. Thermal catalytic oxidation technology relies on catalysts to oxidize and decompose VOCs into CO2 and H2O by heating. The mainstream thermal catalysts are precious metal catalysts and transition metal catalysts. Although precious metal (such as Pt, Pb) catalysts have good low-temperature catalytic activity, the scarcity of precious metal resources and defects such as easy sintering limit their application in the field of thermal catalytic oxidation of VOCs. Transition metal catalysts have the advantages of being cheap, easy to obtain and highly stable, but the catalytic oxidation of VOCs by transition metal catalysts generally has a high ignition temperature, resulting in high system energy consumption. Photocatalytic oxidation technology refers to the process in which electrons of photocatalysts jump from the valence band to the conduction band under the irradiation of light, forming photogenerated electrons in the conduction band and photogenerated holes in the valence band. The reduction-oxidation process of photogenerated electron-hole pairs degrades VOCs, and can also interact with O2 or H2O adsorbed on the catalyst surface to generate superoxide radicals or hydroxyl radicals to oxidize VOCs to CO2 and H2O. TiO2 is currently the most widely studied photocatalyst for treating VOCs due to its excellent ultraviolet light response, strong oxidizing ability of carriers and good stability. However, the traditional solar TiO2 catalytic degradation of VOCs has the problem of low band gap energy of semiconductor materials and low solar quantum efficiency.
[0004] In order to overcome the problems of high energy consumption of traditional thermal catalysis, low photocatalytic quantum efficiency and narrow spectral response range, scholars at home and abroad have proposed to effectively combine photocatalysis and thermal catalysis technology, use solar energy to provide energy for catalytic reactions, use UV-vis excitation on semiconductor catalysts and the thermal effect of infrared light, effectively use the solar spectrum, and give full play to the photothermal synergy to further improve the reaction rate and optimize the selectivity. In photothermal catalytic technology, the design and development of photothermal catalytic materials is a hot topic and key research. TiO2 is both a commonly used photocatalyst and thermal catalyst, but because its band gap is usually between 3.0-3.2eV, it affects its application in photothermal catalytic reactions. Defective TiO prepared by hydrogenating TiO2 2-x With abundant oxygen vacancies and Ti 3+ Species can extend the light absorption range of TiO2 to the visible light region. Oxygen vacancies can not only promote the separation of photogenerated charge carriers, but also serve as active sites for reactant adsorption, accelerating the activation of reactant molecules. However, TiO2 particles are prone to aggregation, which limits their catalytic activity. Transition metal doping is one of the important means to improve the photocatalytic activity of TiO2. Doping with transition metals, such as manganese (Mn), iron (Fe), copper (Cu) and nickel (Ni), can reduce the band gap of TiO2, reduce the recombination rate of electrons and holes, and expand the spectral response to the near-infrared region, and can serve as an active site to enhance the deep oxidation of VOCs. In particular, Mn has strong full-spectrum light absorption characteristics, good thermal catalytic activity and potential photocatalytic activity, and is a very promising photothermal catalytic material. Appropriate Mn doping can potentially be incorporated into the TiO2 lattice, and doped metal ions can act as charge carrier transport channels. Fan et al. (Journal of Colloid and Interface Science, 2022, 608: 3004-3012) effectively combined TiO2 and MnOx to synthesize a highly active TiO2@MnOx hollow sphere structure photothermal catalyst at 240 °C and a space velocity ratio of 120,000 mL g -1 h -1 Under the conditions of 100 ℃ and 200 ℃, the degradation efficiency of this type of catalyst in a humid and sulfur-containing atmosphere for 0.5 ppm NO and 5 ppm ethyl acetate is 70% and 56%, respectively, and the degradation efficiency for 0.5 ppm NO and 5 ppm toluene is 91% and 72%, respectively. Due to the poor adsorption capacity of this type of thermal photocatalyst, it is only suitable for the degradation of medium and low concentrations of VOCs. Therefore, it is necessary to design a catalyst with a large surface area and good electron transfer efficiency to improve its photothermal catalytic oxidation performance for high concentrations of VOCs. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a catalyst for the adsorption-photothermal synergistic degradation of VOCs. The present invention combines a photocatalytic material TiO2, a thermal catalytic material MnOx and a hollow carbon sphere, uses hollow carbon spheres (GCS) as a supporting skeleton, introduces MnO2 and TiO2 into the GCS by a microwave-hydrothermal method, and then prepares a TiO2@MnO2@GCS multifunctional photothermal catalytic material with a core-shell structure by an in-situ calcination reduction process, constructs a photothermal synergistic catalytic composite system with adsorption, thermal catalysis and photocatalysis, which can not only overcome the problems of high energy consumption and low photocatalytic quantum efficiency of traditional thermal catalysis, but also can efficiently degrade VOCs.
[0006] A catalyst for adsorption-photothermal synergistic degradation of VOCs, the catalyst uses hollow carbon spheres as a supporting skeleton, and uses manganese oxide and titanium oxide as active ingredient layers to sequentially coat the hollow carbon spheres to obtain TiO2@MnOx@GCS, wherein the active ingredient layer manganese oxide is located between the active ingredient layer titanium oxide and the hollow carbon spheres.
[0007] A method for preparing a catalyst for adsorption-photothermal synergistic degradation of VOCs comprises the following steps:
[0008] (1) adding an oxalic acid solution to an aqueous solution of potassium permanganate, and then adding graphitized hollow carbon spheres, stirring, and transferring to a hydrothermal reactor for hydrothermal reaction, cooling and filtering, washing and drying the solid mixture, and calcining under an inert gas to obtain graphitized carbon microspheres loaded with manganese dioxide;
[0009] (2) The obtained carbon microspheres loaded with manganese dioxide are immersed in an anhydrous ethanol solution of butyl titanate and ammonia water, heated in a water bath and stirred for reaction, then centrifuged and washed, and finally vacuum dried to obtain TiO2@MnOx@GCS.
[0010] The preparation method of the graphitized hollow carbon spheres comprises: mixing glucose, hexadecyltrimethylammonium bromide and deionized water and stirring them uniformly, performing a hydrothermal reaction in a hydrothermal kettle, filtering and washing after the reaction to obtain a filtrate, placing the filtrate in a tubular furnace, passing a protective gas, and then calcining at a high temperature to obtain carbon microspheres;
[0011] The mass ratio of glucose to hexadecyltrimethylammonium bromide is 2.7:1, the temperature of the hydrothermal reaction is 160-180° C., and the reaction time is 7-9 hours.
[0012] In the step (1), the concentration ratio of potassium permanganate to oxalic acid is 8:10, the molar ratio of graphitized hollow carbon spheres to potassium permanganate is 30:1, the temperature of the hydrothermal reaction is 180°C, the reaction time is 10 to 12 hours, the volume ratio of butyl titanate to ammonia water is 25:3, and the calcination temperature is 400°C.
[0013] In step (3), the water bath heating and stirring reaction time is 5-8 hours, the drying temperature is 60° C., and the drying time is 10 to 12 hours.
[0014] A method for preparing a catalyst for adsorption-photothermal synergistic degradation of VOCs and application of the prepared catalyst in a honeycomb-shaped lightweight VOCs photocatalytic purifier.
[0015] It includes a reactor shell and a honeycomb mesh frame, wherein the reactor shell includes a front split air inlet area and a rear air outlet area, a reaction area is between the air inlet area and the air outlet area, the reaction area is a columnar octagon, and both the air inlet area and the air outlet area are conical structures, and the cross-sectional area is not greater than the cross-sectional area of the reaction area;
[0016] The honeycomb mesh frame is embedded in the column of the reaction zone. Multiple rows of interconnected reaction chambers are fixedly arranged inside the honeycomb mesh frame. Gas enters from the air inlet and then flows into the reaction chamber. Each reaction chamber is a regular hexagonal columnar structure. A double-layer hollow regular hexagonal columnar plate is set inside the reaction chamber, wherein the inner layer is a photocatalyst plate made of the TiO2@MnOx@GCS, and the outer layer is a porous carbon plate. A cylindrical ultraviolet lamp tube is fixed at the center of the reaction chamber to provide an effective light source for the reaction. The ultraviolet lamp tube is connected to the photocatalyst plate through a bracket at the rear of the ultraviolet lamp tube.
[0017] An ultraviolet lamp end cover bracket is also provided between the reaction zone and the gas outlet zone. The end of the reaction area is embedded in the honeycomb mesh frame to tightly cover each reaction chamber unit structure, forming a dense space environment inside. There are dense small holes on the cover surface, so that the gas after the reaction passes through the small holes to the conical exhaust zone and then is discharged from the exhaust port; the ends where the air inlet of the air inlet zone and the air outlet of the air outlet zone are located are quadrilateral shapes.
[0018] The beneficial effects of the present invention are as follows:
[0019] (1) The TiO2@MnOx@GCS multifunctional photothermal catalytic material prepared by the present invention can efficiently adsorb and enrich industrial VOCs of variable concentrations, and effectively convert all light into thermal energy, thereby stimulating TiO2 photocatalysis and MnOx all-light-driven thermal catalysis to produce a photothermal synergistic effect and efficiently degrade VOCs. This not only overcomes the problems of high energy consumption and low photocatalytic quantum efficiency of traditional thermal catalysis, but also solves the problem of large fluctuations in industrial VOCs concentration and high moisture content, which lead to low catalytic performance.
[0020] (2) In order to control the morphology of Mn in the TiO2@MnOx@GCS catalyst to improve the photothermal synergistic effect, based on the influence of different forms of MnO2 on the photothermal catalytic performance, the surfactant SDBS is introduced to directionally control the morphology of MnO2 during the catalyst synthesis process. The microwave-assisted preparation can improve the dispersion of Mn and Ti on the surface of carbon balls, improve the generation and redox performance of lattice oxygen, and realize the controllable preparation of the catalyst. (3) The honeycomb-shaped lightweight VOCs photocatalytic purifier designed by the present invention can efficiently utilize space to fully receive and utilize light energy through the honeycomb mesh structure. It has the advantages of large space utilization, small reactor volume, and high VOCs removal efficiency, and is suitable for a variety of indoor occasions and special confined spaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the working of the present invention;
[0022] Figure 2 It is a schematic diagram of the AA cross-sectional structure of the present invention;
[0023] Figure 3 It is a schematic diagram of the main structure of the present invention;
[0024] Figure 4 It is a schematic diagram of the BB structure of the present invention;
[0025] Figure 5 This is a schematic diagram of the end cover bracket structure of the present invention;
[0026] Figure 6 The SEM, HRTEM images and crystal structure diagrams of the four crystal forms of MnO2;
[0027] Figure 7 The photothermal catalytic performance of four crystal forms of MnO2;
[0028] Figure 8 The photocatalytic performance of α-MnO2 synthesized with different concentrations of SDBS;
[0029] Fig. 9 The photothermal catalytic performance of α-MnO2 prepared by different methods;
[0030] Fig.10 The photothermal catalytic performance of the αβ-MnO2 mixed crystal;
[0031] Fig.11 The photothermal catalytic performance of the αδ-MnO2 mixed crystal;
[0032] Fig.12 The photothermal catalytic performance of the αγ-MnO2 mixed crystal;
[0033] Fig.13Comparison of photothermal catalytic performance of different mixed crystal forms;
[0034] Fig.14 The photothermal performance of Mn / GCS catalyst under different light intensities;
[0035] Fig.15 The corresponding temperature of light conversion to heat of Mn-6 / GCS catalyst under different light intensities;
[0036] Fig.16 Comparison of the photocatalytic, thermal and photothermal catalytic performance of Mn-6 / GCS catalyst under different light intensities;
[0037] Fig.17 The effect of different moisture contents on the photothermal catalytic performance of Mn-6 / GCS catalyst;
[0038] Fig.18 is the thermal catalytic toluene conversion rate of Mn / GCS catalyst at different temperatures;
[0039] Fig.19 CO2 selectivity in the thermal catalytic oxidation of toluene over Mn / GCS catalyst at different temperatures;
[0040] Fig. 20 The morphological characteristics of Mn / GCS catalyst;
[0041] Fig.21 is the EDX spectrum of Mn-6 / GCS catalyst;
[0042] Fig. 22 The photothermal catalytic performance of different catalysts;
[0043] Fig.23 The upper picture is the SEM of TiO2@MnOx@GCS catalyst, and the lower picture is the high-angle annular dark-field scanning transmission electron microscope element mapping image. Specific implementation plan
[0044] The present invention is further described below by way of examples, but the present invention is not limited by the examples.
[0045] Comparative Example 1:
[0046] Steps for preparing carbon sphere-loaded titanium dioxide TiO2@GCS:
[0047] (1) Preparation of carbon microsphere template: 2.7 g of glucose, 1 g of hexadecyltrimethylammonium bromide and 50 mL of deionized water were mixed and stirred evenly, and a hydrothermal reaction was carried out in a hydrothermal reactor. After the reaction, the filtrate was filtered and washed to obtain a filtrate, and the filtrate was placed in a tubular furnace and passed with a protective gas and then calcined to obtain carbon microspheres;
[0048] (2) Preparation of carbon microspheres loaded with titanium dioxide TiO2@GCS: 20 mg of carbon microspheres were soaked in 250 μL of pure butyl titanate and 0.3 mL of ammonia water, mixed and dissolved in 50 ml of anhydrous ethanol solution, heated in a water bath and stirred for 5-8 hours, then centrifuged and washed, and vacuum dried at 60°C for 12 hours to obtain carbon microspheres loaded with titanium dioxide TiO2@GCS. Comparative Example 2:
[0049] Preparation of carbon spheres loaded with manganese dioxide MnO x @GCS steps:
[0050] (1) Preparation of carbon microsphere template: 2.7 g of glucose, 1 g of hexadecyltrimethylammonium bromide and 50 mL of deionized water were mixed and stirred evenly, and a hydrothermal reaction was carried out in a hydrothermal reactor. After the reaction, the filtrate was filtered and washed to obtain a filtrate, and the filtrate was placed in a tubular furnace and passed with a protective gas and then calcined to obtain carbon microspheres;
[0051] (2) Preparation of carbon microspheres loaded with manganese dioxide: 1.27 g (0.008 mol) of potassium permanganate was dissolved in 100 mL of deionized water to prepare a solution with a concentration of 0.08 mol / L, and 0.50 g (0.002 mol) of sodium thiosulfate pentahydrate was dissolved in 100 mL of deionized water to prepare a solution with a concentration of 0.02 mol / L. The sodium thiosulfate solution was slowly added to the potassium permanganate solution under stirring. After thorough mixing, 30 mL of the mixed solution was placed in a beaker, and the carbon spheres obtained in step (1) were added to make the molar ratio of carbon microspheres to potassium permanganate be 30:1. After thorough stirring, the mixture was transferred to a hydrothermal reactor and subjected to hydrothermal reaction at a temperature of 110-120° C. for 10-12 hours. The mixture was cooled naturally and solid-liquid separation was performed using a sand core funnel. The solid was washed with deionized water and anhydrous ethanol in turn and dried to obtain carbon microspheres loaded with manganese dioxide MnO2@GCS.
[0052] Comparative Example 3:
[0053] MnO2 can be deposited under different conditions to obtain different crystal forms:
[0054] MnO2 has different crystal forms, which can be obtained by changing the precursor, hydrothermal time and temperature. Specifically, the preparation methods of α-MnO2, δ-MnO2, β-MnO2 and γ-MnO2 are:
[0055] Preparation method of α-MnO2: 1.25g KMnO4 and 0.53g MnSO4·H2O are dissolved in 80ml deionized water, magnetically stirred for 30min to form a uniform suspension, and placed in a hydrothermal kettle for hydrothermal reaction, wherein the reaction temperature is 160°C and the reaction time is 12h. After the reaction, the suspension is cooled to room temperature and filtered and washed. The washed filtrate is placed in an oven at 80°C and dried for 2h, and then calcined at 360°C for 2h to obtain α-MnO2.
[0056] Preparation method of δ-MnO2: 1.50g KMnO4 and 0.28g MnSO4·H2O are dissolved in 80ml deionized water, and magnetically stirred for 30min to form a uniform suspension. The suspension is placed in a hydrothermal kettle for hydrothermal reaction, wherein the reaction temperature is 160°C and the reaction time is 12h. After the reaction, it is cooled to room temperature and filtered and washed. The washed filtrate is placed in an oven at a temperature of 80°C and dried for 2h, and then calcined at 360°C for 2h to obtain δ-MnO2.
[0057] Preparation method of β-MnO2: 1.69g MnSO4·H2O and 2.28g (NH4) 2S2O8 are dissolved in 80ml deionized water, and magnetically stirred for about 30min to form a uniform suspension. The suspension is placed in a hydrothermal kettle for hydrothermal reaction, wherein the reaction temperature is 140°C and the reaction time is 12h. After the reaction, it is cooled to room temperature and filtered and washed. The washed filtrate is placed in an oven at a temperature of 80°C and dried for 2h, and then calcined at 360°C for 2h to obtain β-MnO2.
[0058] Preparation method of γ-MnO2: 3.38g MnSO4·H2O and 4.58g (NH4) 2S2O8 are dissolved in 80ml deionized water, and magnetically stirred for about 30min to form a uniform suspension. The suspension is placed in a hydrothermal kettle for hydrothermal reaction, wherein the reaction temperature is 90°C and the reaction time is 24h. After the reaction, it is cooled to room temperature and filtered and washed. The washed filtrate is placed in an oven at a temperature of 80°C and dried for 2h, and then calcined at 360°C for 2h to obtain γ-MnO2.
[0059] Figure 6 The SEM, HRTEM images and crystal structure diagrams of four types of MnO2, α, β, δ and γ, are shown in Figure 2. Figure 6 (a), (b) and (c) are SEM, HRTEM images and crystal structure diagrams of α-MnO2; Figure 7 (d), (e) and (f) are SEM, HRTEM images and crystal structure diagrams of β-MnO2;
[0060] Figure 6(g), (h) and (I) are SEM, HRTEM images and crystal structure diagrams of γ-MnO2; Figure 6 (j), (k) and (l) are SEM, HRTEM images and crystal structure diagrams of δ-MnO2.
[0061] The photothermal catalytic activities of four crystalline forms of MnO2, α, β, δ and γ, were tested respectively. Figure 7 As shown, γ-MnO2 has a higher conversion rate of toluene and better photothermal catalytic activity.
[0062] Furthermore, α-MnO2 can be prepared by SDBS-assisted wet precipitation method or by non-SDBS-assisted wet precipitation method.
[0063] The preparation process of α-MnO2 by SDBS-assisted wet precipitation is as follows:
[0064] (1) 2.37 g (15 mmol) of KMnO4 was dissolved in 35 mL of deionized water under strong magnetic stirring to obtain a KMnO4 solution; different molar concentrations of sodium dodecylbenzenesulfonate (SDBS) (1 mmol, 3 mmol, 6 mmol, 9 mmol) and 15 mL of deionized water were ultrasonically stirred in a 100 mL two-necked flask for 15 min to form a transparent emulsion.
[0065] (2) The completely dissolved KMnO4 solution was transferred to the continuously stirred emulsion. After the two were mixed, the mixed solution was sealed in a flask and heated at 85°C with continuous stirring for 2 h.
[0066] (3) Add 0.5 mL of 98% sulfuric acid (H2SO4) solution into the flask and stir for 2 h. Finally, collect the suspension by filtration, wash with ethanol and deionized water, and dry at 105°C for 12 h to obtain α-MnO2.
[0067] The photothermal catalytic activity of α-MnO2 synthesized by SDBS at different concentrations was tested. The test results are as follows: Figure 8 It was shown that the α-MnO2 prepared using 6 mmol of sodium dodecylbenzene sulfonate (SDBS) had a higher conversion rate for toluene and better photothermal catalytic activity.
[0068] The preparation process of α-MnO2 without adding SDBS is as follows:
[0069] (1) Dissolve 2.37 g (15 mmol) of KMnO4 in 35 mL of deionized water under strong magnetic stirring to obtain a KMnO4 solution;
[0070] (2) Mix 0.5 mL of 98% sulfuric acid (H2SO4) solution with KMnO4 solution, stir for 2 h, and finally collect the suspension by filtration. Wash it with ethanol and deionized water, and dry it at 105°C for 12 h to obtain α-MnO2.
[0071] The photothermal catalytic activity of α-MnO2 prepared by different methods was tested. The test results are as follows: Fig. 9 Among them, the α-MnO2 prepared by SDBS-assisted wet precipitation method has a higher conversion rate to toluene and better photothermal activity. Comparative Example 4:
[0072] Preparation of mixed crystals:
[0073] Similarly, the precursor, hydrothermal temperature and time are controlled to obtain homogeneous MnO2 with different mixed crystal forms.
[0074] (1) αδ-MnO2
[0075] KMnO4 and hydrated manganese sulfate (MnSO4·H2O) in different molar ratios were dissolved in 120 mL of deionized water and stirred vigorously for 0.5 h to form a uniform suspension. The mixed solution was then immediately moved to a 150 ml Teflon-lined stainless steel autoclave, sealed, and placed in an oven at 160 ° C for 12 h. After cooling to room temperature, the resulting precipitate was collected, filtered, and washed with distilled water until the pH value of the filtrate was close to 7. Finally, all products were stored at 60 ° C for 24 h and calcined at 350 ° C for 2 h.
[0076] (2) αβ-MnO2
[0077] Dissolve 3.16g KMnO4 and 4.536g H2C2O4·2H2O (oxalic acid) in 35ml distilled water and stir to form a uniform solution. While stirring, drop the H2C2O4·2H2O solution into the KMnO4 solution and keep it at 60℃ for 30min to form a uniform solution, then transfer it into a teflon-lined stainless steel autoclave (100mL) and heat it to 180℃ in an oven for 12h. Collect, wash, filter, dry at 80℃, and then calcine at 400℃ for 5h.
[0078] (3) αγ-MnO2
[0079] A two-step hydrothermal method was used to dissolve 3.38g MnSO4·H2O and 4.58g (NH4)2S2O8 in 80ml deionized water, and magnetic stirring was performed for about 30min to form a uniform suspension. The hydrothermal autoclave was heated at 90℃ for 24h, and all products were dried at 80℃ for 4h, and calcined at 360℃ for 2h to obtain γ-MnO2. A certain weight of γ-MnO2 was weighed, and a two-step hydrothermal method was used to synthesize the homogeneous structure of α-MnO2 and γ-MnO2. KMnO4 and MnSO4·H2O in a certain molar ratio were dissolved in 80ml deionized water, and magnetic stirring was performed for about 30min to form a uniform suspension. The hydrothermal autoclave was heated at 160℃ for 12h, and all products were dried at 80℃ for 4h, and calcined at 360℃ for 2h to obtain αγ-MnO2.
[0080] The photothermal catalytic activity of mixed crystalline MnO2 prepared by different methods was tested, and the test results are as follows: Figure 10-13 As shown, αβ-MnO2 has a higher conversion rate for toluene and better photothermal catalytic activity.
[0081] Comparative Example 5:
[0082] Furthermore, the different manganese contents also lead to different photothermal catalytic effects.
[0083] Preparation method of carbon spheres loaded with manganese with different contents:
[0084] Preparation of graphitized carbon balls GCS: 6.16 g of glucose and 0.4 g of CTAB were dissolved in 60 mL of deionized water, and ultrasonicated for 30 min until the solution became transparent. The mixed solution was transferred to a 100 mL hydrothermal kettle, reacted at 180 °C for 9 h, cooled to room temperature and filtered, washed alternately with deionized water and ethanol, and the filtered product was dried in an oven at 80 °C to obtain CS. CS was placed in a tubular furnace under nitrogen protection, raised to 900 °C at 5 °C / min, kept warm for 3 h, and naturally cooled to room temperature to obtain graphitized carbon balls GCS.
[0085] Preparation of Mn-x / GCS: 0.1 g GCS and x mmol KMnO4 were dissolved in 200 mL deionized water, and ultrasonic treatment was performed until the mixture was uniformly mixed. The mixed solution was transferred to three 100 mL hydrothermal kettles, and reacted at 140 °C for 5 h. After cooling to room temperature, the mixture was filtered, washed with ethanol and water, and the filtered product was dried in an oven at 80 °C to obtain a fresh catalyst Mn-x / GCS, where x represents the amount of potassium permanganate added.
[0086] Further, according to the above steps for preparing Mn-x / GCS, the molar amount x of potassium permanganate is changed to 2mmol, 4mmol, 6mmol, 8mmol, and 10mmol to prepare catalysts Mn-2 / GCS, Mn-4 / GCS, Mn-6 / GCS, Mn-8 / GCS, and Mn-10 / GCS, respectively. Table 1 lists the physical data of carbon microspheres loaded with manganese; Table 2 shows the elemental composition and valence of carbon microspheres loaded with manganese:
[0087] Table 1
[0088]
[0089] Table 2
[0090]
[0091] The photothermal catalytic activity of carbon sphere-supported manganese was tested. Figure 14-17 As shown, the conversion rate of Mn-6 / GCS is higher, and the photothermal catalytic process is dominated by heat. When Mn-6 / GCS was tested, the light intensity was different, and the corresponding temperature of the Mn-6 / GCS catalyst for light conversion to heat was different. The stronger the light intensity, the higher the thermal temperature of the conversion, and the temperature tends to be stable after the conversion; under the same light intensity, the photothermal catalytic performance of the Mn-6 / GCS catalyst is higher.
[0092] like Figure 17-18 As shown, the thermal catalytic activity of carbon microspheres loaded with manganese was tested. The test was continuously conducted for 50 hours under dry air. When the temperature was greater than 200°C, the conversion rates of toluene and CO were stable at more than 95%, and the catalytic activity was stable. At the same temperature, the conversion rate of Mn-6 / GCS for toluene and CO was higher.
[0093] Comparative Example 6:
[0094] Preparation of MnOx@TiO2@GCS, the preparation steps are:
[0095] (1) 3.38 g of MnSO4·H2O and 4.58 g of (NH4)2S2O8 were dissolved in 80 ml of deionized water and stirred magnetically for about 30 min to form a uniform suspension. The suspension was placed in a hydrothermal reactor for hydrothermal reaction at 90°C for 24 h. After thorough mixing, 30 mL of the mixture was placed in a beaker.
[0096] (2) The mixed solution was added with the carbon microspheres loaded with titanium dioxide obtained in Comparative Example 1 to make the carbon microspheres loaded with titanium dioxide and Mn 2+The molar ratio of the two is 30:1. After being fully stirred, the mixture is transferred to a hydrothermal reactor and subjected to a hydrothermal reaction at 120°C for 12 hours. The mixture is naturally cooled and a sand core funnel is used for solid-liquid separation. The solid is washed with deionized water and anhydrous ethanol in turn and then dried to obtain MnOx@TiO2@GCS. XRD detection shows that the manganese dioxide in the carbon microsphere-loaded manganese dioxide is γ-MnO2.
[0097] Embodiment 1:
[0098] Preparation of TiO2@MnOx@GCS, the preparation steps are:
[0099] (1) Preparation of carbon microsphere template: 2.7 g of glucose, 1 g of hexadecyltrimethylammonium bromide and 50 mL of deionized water were mixed and stirred evenly, and a hydrothermal reaction was carried out in a hydrothermal reactor. After the reaction, the filtrate was filtered and washed to obtain a filtrate, and the filtrate was placed in a tubular furnace and passed with a protective gas and then calcined to obtain carbon microspheres;
[0100] (2) Preparation of carbon microspheres loaded with manganese dioxide: 0.948 g (8 mmol) of KMnO4 was dissolved in 35 mL of deionized water under strong magnetic stirring to obtain a KMnO4 solution;
[0101] 1.361 g of H2C2O4·2H2O solution was dropped into KMnO4 solution, and kept at 60°C for 30 min to form a uniform solution. The carbon microspheres obtained in step (1) were added so that the molar ratio of carbon microspheres to potassium permanganate was 30:1. After sufficient stirring, the mixture was transferred to a teflon-lined stainless steel reactor and heated to 180°C in an oven for 12 h. The mixture was collected and washed at 80°C, and solid-liquid separation was performed using a sand core funnel. The solid was washed with deionized water and anhydrous ethanol in turn, dried, and then calcined at 400°C after passing a protective gas for 5 h to obtain carbon microspheres loaded with manganese dioxide MnO2@HCS.
[0102] (3) The carbon microspheres loaded with manganese dioxide obtained in step (2) are immersed in 0.25 mL of pure butyl titanate and 0.3 mL of 28% ammonia water, mixed and dissolved in 50 mL of anhydrous ethanol solution, heated in a water bath with stirring for 5 to 8 hours, then centrifuged and washed, and vacuum dried at 60° C. for 10 to 12 hours to obtain TiO2@MnOx@GCS.
[0103] Further, if Figure 19-22 As shown, the materials TiO2@GCS, MnOx@GCS, MnOx@TiO2@GCS, and TiO2@MnOx@GCS prepared in Comparative Examples 1 to 5 and Example 1 were heated to 290 mW / cm 2Under the conditions of an air velocity ratio of 30000ml / g / h, the VOCs purification effect was tested under light adjustment. According to the test results, titanium doping improved the photothermal catalytic performance, and TiO2@MnOx@GCS catalyst had the best effect in purifying VOCs.
[0104] Embodiment 2:
[0105] like Figure 1-5 As shown, a catalyst for adsorption-photothermal synergistic degradation of VOCs can be used in a honeycomb lightweight VOCs photocatalytic purifier, the purifier includes a reactor shell and a honeycomb mesh frame, the reactor shell includes a front split air inlet area and a rear air outlet area, the air inlet area and the air outlet area are between the reaction zone, the reaction zone is a columnar octagon, the ends where the air inlet of the air inlet zone and the air outlet of the air outlet zone are located are quadrilateral shapes, the air inlet zone and the air outlet zone are both conical structures, and the cross-sectional areas are not larger than the cross-sectional area of the reaction zone.
[0106] Furthermore, a honeycomb mesh frame is embedded in the column of the reaction zone, and multiple rows of interconnected reaction chambers are fixedly arranged inside the honeycomb mesh frame. The gas enters from the air inlet and then is diverted into the reaction chamber. Each reaction chamber is a regular hexagonal columnar structure, and a double-layer hollow regular hexagonal columnar plate is set inside the reaction chamber, wherein the inner layer is a photocatalyst plate made of TiO2@MnOx@GCS of Example 1, and the outer layer is a porous carbon plate. The inner and outer layers can be used as catalysts and adsorbents for photocatalytic VOCs. A cylindrical ultraviolet lamp 1 that provides an effective light source for the reaction is fixed at the center of the reaction chamber, and the ultraviolet lamp is connected to the photocatalyst plate through a bracket at the rear of the ultraviolet lamp.
[0107] Furthermore, an ultraviolet lamp end cover bracket is provided between the reaction zone and the gas outlet zone. The end of the reaction area is embedded in the honeycomb mesh frame to tightly cover each reaction chamber unit structure, forming a dense space environment inside. There are dense small holes on the cover surface, so that the gas after the reaction passes through the small holes to the conical exhaust zone and is then discharged from the exhaust port.
[0108] Furthermore, the porous carbon material is formed by adding glucose into the hollow carbon spheres to form a micro-carbon sphere structure wrapped inside the hollow carbon spheres after hydrothermal reaction. It is characterized by having a good micro-mesoporous structure and a specific surface area of 1945m 2 / g, pore volume 1.627cm 3 / g, micropore specific surface area is 1134m 2 / g. At 25°C, when the initial toluene concentration is 1000ppm, its dynamic toluene adsorption capacity is 813mg / g, the adsorption efficiency is maintained above 90% and the stability is high, which is suitable for repeated use.
[0109] The photocatalyst plate is composed of TiO2-MnO2 materials. Titanium dioxide is a good ultraviolet light responsive photocatalytic material. The band gap of anatase phase titanium dioxide is 3.2eV. It can effectively remove volatile organic compounds such as toluene under ultraviolet light. The reaction mechanism is as follows: under ultraviolet light, the electrons in the titanium dioxide crystal undergo orbital transitions, generating photogenerated electron-hole pairs, and the electrons combine with surrounding oxygen atoms to form superoxide radicals (·O 2- ), the holes react with the surrounding water to form hydroxyl radicals (·OH), these active free radicals attack the VOCs gas to destroy its structure and then oxidize it, or the photogenerated holes directly react with the VOCs gas to oxidize it.
[0110] The band gap energy of manganese oxide is 1.59eV, and it also has a good response effect to visible light. Under the irradiation conditions of ultraviolet light with higher photon energy (wavelength less than 400nm), it can completely absorb photon energy. Part of it is used for the photoelectric response of manganese oxide to cause electron orbital transition to produce active free radicals, and the other part of the energy is radiated in the form of heat energy to increase the ambient temperature and promote its photothermal synergistic catalytic effect on VOCs.
[0111] When using the VOCs purifier, first, according to Figure 1-5 As shown, the gas enters from the air inlet and then reaches each reaction chamber. Each reaction chamber has a porous carbon plate and a photocatalyst plate. The VOCs gas is first adsorbed into the porous carbon plate, and then irradiated on the photocatalyst plate by ultraviolet light, producing a photothermal effect with manganese dioxide and titanium dioxide, so that the VOCs can be catalytically oxidized and degraded into carbon dioxide and water in the reactor, and finally carried to the exhaust port by the airflow for discharge. Through the adsorption-photothermal catalytic degradation-re-adsorption cycle reaction occurring on the two layers of reaction plates, the VOCs can be continuously catalytically degraded inside the reactor, thereby achieving the purpose of continuously purifying the air.
[0112] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A catalyst for adsorption-photothermal synergistic degradation of VOCs, characterized in that: The catalyst uses hollow carbon spheres as a supporting skeleton, and uses manganese oxide and titanium oxide as active ingredient layers to sequentially coat the hollow carbon spheres to obtain TiO2@MnOx@GCS, wherein the active ingredient layer manganese oxide is located between the active ingredient layer titanium oxide and the hollow carbon spheres.
2. A method for preparing a catalyst for adsorption-photothermal synergistic degradation of VOCs as claimed in claim 1, characterized in that: The following steps are involved: (1) adding an oxalic acid solution to an aqueous solution of potassium permanganate, and then adding graphitized hollow carbon spheres, stirring, and transferring to a hydrothermal reactor for hydrothermal reaction, cooling and filtering, washing and drying the solid mixture, and calcining under an inert gas to obtain graphitized carbon microspheres loaded with manganese dioxide; (2) The obtained carbon microspheres loaded with manganese dioxide were immersed in a mixture of 0.25 mL of pure butyl titanate and 0.3 mL of 28% ammonia water dissolved in 50 mL of anhydrous ethanol solution, heated in a water bath with stirring for reaction, then centrifuged and washed, and finally vacuum dried to obtain TiO2@MnOx@GCS.
3. The method for preparing a catalyst for adsorption-photothermal synergistic degradation of VOCs according to claim 2, characterized in that: The preparation method of the graphitized hollow carbon spheres comprises: mixing glucose, hexadecyltrimethylammonium bromide and deionized water and stirring them uniformly, performing a hydrothermal reaction in a hydrothermal kettle, filtering and washing after the reaction to obtain a filtrate, placing the filtrate in a tubular furnace, passing a protective gas, and then calcining at a high temperature to obtain graphitized hollow carbon spheres.
4. The method for preparing a catalyst for adsorption-photothermal synergistic degradation of VOCs according to claim 3, characterized in that: The mass ratio of glucose to hexadecyltrimethylammonium bromide is 2.7:1, the temperature of the hydrothermal reaction is 160-180° C., and the reaction time is 7-9 hours.
5. The method for preparing a catalyst for adsorption-photothermal synergistic degradation of VOCs according to claim 2, characterized in that: In the step 1, the concentration ratio of potassium permanganate to oxalic acid is 8:10, the molar ratio of graphitized hollow carbon spheres to potassium permanganate is 30:1, the temperature of the hydrothermal reaction is 180°C, the reaction time is 10 to 12 hours, the volume ratio of butyl titanate to ammonia water is 25:3, and the calcination temperature is 400°C.
6. According to the method for preparing a catalyst for adsorption-photothermal synergistic degradation of VOCs according to claim 2, the water bath heating and stirring reaction time in step 2 is 5-8 hours, the drying temperature is 60°C, and the drying time is 10 to 12 hours.
7. Use of the catalyst prepared by the method for preparing a catalyst for adsorption-photothermal synergistic degradation of VOCs as claimed in claim 2 in a honeycomb-shaped lightweight VOCs photocatalytic purifier.
8. A honeycomb lightweight VOCs photocatalytic purifier, characterized in that: It includes a reactor shell and a honeycomb mesh frame, wherein the reactor shell includes a front split air inlet area and a rear air outlet area, a reaction area is between the air inlet area and the air outlet area, the reaction area is a columnar octagon, and both the air inlet area and the air outlet area are conical structures, and the cross-sectional area is not greater than the cross-sectional area of the reaction area; A honeycomb mesh frame is embedded in the column of the reaction zone, and multiple rows of interconnected reaction chambers are fixedly arranged inside the honeycomb mesh frame. Gas enters from the air inlet and then flows into the reaction chamber. Each reaction chamber is a regular hexagonal columnar structure. A double-layer hollow regular hexagonal columnar plate is set inside the reaction chamber, wherein the inner layer is a photocatalyst plate made of the TiO2@MnOx@GCS described in claim 1, and the outer layer is a porous carbon plate. A cylindrical ultraviolet lamp tube is fixed at the center of the reaction chamber to provide an effective light source for the reaction, and the ultraviolet lamp tube is connected to the photocatalyst plate through a rear bracket of the ultraviolet lamp tube; An ultraviolet lamp end cover bracket is also provided between the reaction zone and the gas outlet zone. The end of the reaction area is embedded in the honeycomb mesh frame to tightly cover each reaction chamber unit structure, forming a dense space environment inside. There are dense small holes on the cover surface, so that the gas after the reaction passes through the small holes to the conical exhaust zone and then is discharged from the exhaust port; the ends where the air inlet of the air inlet zone and the air outlet of the air outlet zone are located are quadrilateral shapes.
Citation Information
Patent Citations
Carbon fiber microsphere loaded TiO2 catalyst for adsorption-photodegradation of VOC and preparation method of carbon fiber microsphere loaded TiO2 catalyst
CN110624528A
Preparation method and application of manganese-titanium composite oxide catalytic material with hollow sphere structure assembled by rods
CN114471535A
Preparation method and application of charcoal-loaded MnOx and TiO2 catalytic material
CN116786111A
A honeycomb photocatalytic VOCs treatment device
CN218795005U
Cited By
Waste gas treatment device and method for methyl ethyl ketone peroxide processing
CN121944780A